2019
DOI: 10.5455/javar.2019.f360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nisin and lysozyme on bacteriological and sensorial quality of pasteurized milk

Abstract: Objectives:The objective of this study was to evaluate the impact of the antimicrobials nisin and lysozyme to control the growth of spoilage bacteria of pasteurized milk during cold storage. Materials and Methods:Nisin, lysozyme, and a mixture of them were inoculated into freshly pasteurized milk at 500 IU/ml concentrations each. The acidity, sensory evaluation, and bacteriological quality of the treated pasteurized milk samples were examined at zero time and every 3 days till the samples showed the signs of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Similar studies performed on different dairy products also reported that the addition of lactoferrin (Zakaria et al, 2020), lysozyme (Saad et al, 2019), and natamycin (Nottagh et al, 2020) had no adverse effects on the sensory properties of products.…”
Section: Sensory Evaluationsupporting
confidence: 63%
“…Similar studies performed on different dairy products also reported that the addition of lactoferrin (Zakaria et al, 2020), lysozyme (Saad et al, 2019), and natamycin (Nottagh et al, 2020) had no adverse effects on the sensory properties of products.…”
Section: Sensory Evaluationsupporting
confidence: 63%
“…Nisin (E234) is one of the most examined bacteriocins used as an inhibitory agent of potentially pathogenic bacteria that proliferate in the food industry [1][2][3]. Bacteriocins are relatively small antimicrobial peptides ribosomally synthesized by most known bacteria, e.g., Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased concern over synthetic preservatives, the prevalence of foodborne pathogens with resistance to classical antibiotics, restrictions or prohibition of the use of some chemical preservatives in some countries, and increased consumer tendency for fresh or minimally processed foods have created many technological challenges in the food industry (58). Therefore, it is necessary to study and investigate new natural antimicrobial compounds with a broad spectrum of antimicrobial activity (62) or to find ways to increase the effectiveness of the compounds or methods used (39).…”
mentioning
confidence: 99%